VISUAL REPRESENTATION OF JUVENILE DELINQUENCY: A SEMIOTIC STUDY OF THE FILM 'GALAKSI' BY KUNTZ AGUS - Maharani, Cintya Putri; Rahmawati, Laili Etika (International Journal of Cultural and Social Science, 2025)
Juvenile delinquency is a complex and multidimensional social phenomenon, thus attracting the attention of many parties, including experts, policy makers, and the general public. This study provides insight into how film media influences public perceptions and attitudes towards social issues, particularly juvenile delinquency. By examining the semiotic representation in "Galaksi", this study contributes to a deeper understanding of how films construct and communicate social narratives about juvenile behavior. This study aims to analyze the representation of juvenile delinquency in the film "Galaksi" (2023) using Ferdinand de Saussure's semiotic approach and Stuart Hall's theory of representation. Specifically, this study seeks to: Identify elements in the film that represent juvenile delinquency & Explore the signifiers and signifieds used to depict juvenile delinquency. This study uses a descriptive qualitative approach within the constructivist paradigm. Data collection techniques include film analysis and open-ended interviews, with source triangulation used to ensure data validity. An inductive approach is applied to build a comprehensive understanding of the representation of juvenile delinquency in film media. This study refers to Ferdinand de Saussure's semiotic theory, which examines the relationship between the signifier (the physical form of the sign) and the signified (conceptual meaning), and Stuart Hall's representation theory to analyze how meaning is constructed and communicated through cultural texts. This study aims to determine what elements in the film 'Galaksi' represent juvenile delinquency based on Ferdinand De Saussure's semiotic theory and to determine what signifiers and signifieds are used in the film 'Galaksi'.